Integration of physiology in a curriculum on human structure: a snapshot of the cardiovascular block - Bassey, Rosemary B.; Hill, Robert V.; Rennie, William P. (Frontiers in Physiology, 2023)
With the gradual shift from discipline-based to competency-based medical education, the integrated curriculum has become a popular model for connecting basic science and clinical content in undergraduate medical education. Despite its popularity, there are concerns that important physiological concepts are not adequately addressed. We describe the spiral integration of physiology content in the 5-week Cardiovascular block of our Homeostasis course at the Zucker School of Medicine. We also describe our approach to incorporating physiology into an integrated, constructed response, short-answer assessment format. Our approach to spiral integration consists of rotating lab stations that highlight the distinction between normal and abnormal states, linked with appropriate clinical interventions. Physiology is at the core of integration in any curriculum and the basis of all applied fields of medicine, hence our approach is that teaching structural relationships would not be valuable without consideration of its functions, which can then be utilized in discussion of clinical presentations, imaging, and relevant pathologies. Likewise, our integrated assessments require the students to compose their answers to the questions from scratch, which creates a shift in mode of students' preparation from rote memorizations to more cognitive processing that enhances critical thinking.